Validation and utility of the French version of the Unified Multidimensional Calling Scale (UMCS-22) for stipended volunteer firefighters - Marina Burakova (PLoS ONE, 2026)
This study evaluated the psychometric properties of the French version of the Unified Multidimensional Calling Scale (UMCS-22), adapted for use with volunteer firefighters, including reliability, construct and criterion validity. Data were collected electronically via LimeSurvey (N = 1,149) and analysed using Jamovi 2.3.3. The measurement model of the French UMCS-22, examined globally and with respect to measurement invariance across gender and age groups, exhibited strict invariance. Internal consistency coefficients ω-McDonald of the dimensional scores of the French UMCS-22 fell between.75 and.86; while its global score had ω = .96. The evaluation of criterion validity through Bayesian linear regression and Structural equation modelling demonstrated differential functioning of the French UMCS-22 facets. Specifically, transcendent summons and pervasiveness were associated with the negative outcomes and purposefulness did not predict any outcome. The utility of the French UMCS-22 adapted for stipended volunteer firefighters is discussed with regard to the neoclassical and modern approaches as well as with regard to the double-edged sword nature of calling.